2020
DOI: 10.1039/d0tb00616e
|View full text |Cite
|
Sign up to set email alerts
|

HBC-nanofiber hydrogel scaffolds with 3D printed internal microchannels for enhanced cartilage differentiation

Abstract: HBC-nanofiber hydrogel scaffolds with 3D printed internal microchannels have been developed to provide a multifunctional biomimetic microenvironment for hMSC chondrogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…The nanofiber loaded hydrogels showed the presence of key components of the cartilage matrix, that is, glycosaminoglycans (GAG) and collagen II, indicating the differentiation of hMSCs. However, the hydrogel lacks sufficient mechanical strength of native cartilage, and hence PCL was used to provide the framework of a 3D volumetric complex 128 …”
Section: Electrospun Nanofiber Reinforced Composites For the Delivery Of Small Molecules Genes And Proteins In Multiple Ailmentsmentioning
confidence: 99%
“…The nanofiber loaded hydrogels showed the presence of key components of the cartilage matrix, that is, glycosaminoglycans (GAG) and collagen II, indicating the differentiation of hMSCs. However, the hydrogel lacks sufficient mechanical strength of native cartilage, and hence PCL was used to provide the framework of a 3D volumetric complex 128 …”
Section: Electrospun Nanofiber Reinforced Composites For the Delivery Of Small Molecules Genes And Proteins In Multiple Ailmentsmentioning
confidence: 99%
“…The study outcome suggested that the developed scaffold system exhibited excellent proliferation and differentiation of the cells which indicates their performance in cartilage tissue engineering [135]. A recent study reported by Liu and co-workers have demonstrated the fabrication of poly(ε-caprolactone) (PCL) framework reinforced with poly(lactic-co-glycolic acid) (PLGA) electrospun nanofiber incorporated hydroxybutyl chitosan (HBC) hydrogels [136]. Briefly, PLGA nanofibers have been prepared through electrospinning and fragmented through an aminolysis degradation reaction.…”
Section: Cartilage Tissue Engineeringmentioning
confidence: 99%
“…Figure 11 clearly indicates the preparation process and differentiation of the human mesenchymal stem cells (hMSCs) in vitro and cartilage regeneration in vivo. Especially, the in vivo study demonstrated significant induction of cartilage differentiation of the hMSCs [136]. Therefore, it is well evidenced that efforts have been continuously made on the fabrication of scaffolds by adopting different strategies and materials with various architecture in order to achieve enhanced cartilage regeneration.…”
Section: Cartilage Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…For repair or regeneration purposes, biomedical scaffolds are often indicated as an advantageous solution as they can provide a 3D framework to enable cell proliferation, matrix deposition, and consequent tissue regeneration [11]. From work published in this area, the most common natural materials used in such devices are collagen, agarose, chitosan, hyaluronic acid, fibrin, and alginate [12][13][14].…”
Section: Introductionmentioning
confidence: 99%